Dry-land bilateral hand-force production and swimming performance in paralympic swimmers - Dingley, A. A.; Pyne, D.; Burkett, B. (International Journal of Sports Medicine, 2014)
The effectiveness of human movement is the culmination of several musculoskeletal factors; asymmetry in movement could reduce optimal performance. The aims of this study were to quantify relationships between bilateral hand-force production, swimming performance, and the influence of fatigue. Paralympic swimmers (n=21, aged 20.9 ± 4.7 yr) were categorised into no, high- and low-range physical disability groups and performed two 100 m time trials to measure swimming performance. Bilateral hand-force was measured over two 60 s maximal tests on a swim-bench ergometer to quantify the degree of asymmetry. Large relationships between mean force and swimming velocity were seen for both the high- (r=0.62, ±0.45; r-value, ±90% confidence limits) and low-range (r=0.62, ±0.50) groups. Asymmetry was related to level of disability, with the smallest difference of 6.7, ±2.6 N in the no-musculoskeletal disability group. This difference increased to 13.1, ±10.0 N and 13.5, ±16.2 N in the high- and low-range groups. Between the first and last 15 s of the swim-bench test, reductions in mean force were small for the physical disabilities groups. Similarly, changes in asymmetry were small for both the no-physical and low-range groups. Paralympic swimmers with a more severe physical impairment typically generate substantially lower force and velocity.